PENERAPAN METODE REAP (READ, ENCODE, ANNOTATE, PONDER) BERBANTUAN TEKS BERWARNA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN PANYINGKIRAN 1 KABUPATEN SUMEDANG - Novitasari, Nina; Djuanda, Dadan; Maulana, Maulana (Jurnal Pena Ilmiah, 2019)
The result used the PTK method and the research design refers to the Kemmis and Taggart models which consist of planning, action, observation and reflection. This research is motivated by the ability of students who are still low when learning on reading comprehension skills. When observing in class IV of Panyingkiran 1 Elementary School, seen from the learning outcomes there were still many who had not yet reached the KKM, which was 72. To improve the condition, the color-assisted REAP method was applied. First cycle, students who completed 12 or 52%, 11 or 48% of students didn’t complete. Cycle II, students who completed as many as 17 or 74%, which has not been completed as many as 6 or 26%. Cycle III, 87% or 20 students completed, while 13% or 3 students weren’t completed. Thus, it is evident that the application of color-assisted REAP methods can improve the learning outcomes of students' reading comprehension skills.